Animal bite wound categories, their determinants and health seeking behaviors among patients presenting to the anti-rabies clinic at a tertiary care hospital of Kathmandu: a mixed methods study. - Mishra, Abadhesh Kumar; Bhandary, Shital (Journal of General Practice and Emergency Medicine of Nepal, 2022)
Introduction: Rabies, an invariably fatal viral disease, is transmitted to humans through animal bites, most commonly dogs. There is little information about categories of wounds due to animal bites, their determinants and health seeking behaviors in Nepal. This study aims to find out different categories of the animal bite wounds, their determinants and health seeking behaviors among the patients presenting to the anti-rabies clinic at Sukraraj Tropical and Infectious Disease Hospital, Kathmandu.Method: This study is based on concurrent, triangulation (quantitative dominant) mixed method design. Those animal bite cases who attended Sukraraj Tropical and Infectious Disease Hospital were the participants of the study. Data was collected purposively for 1 week and total number of respondents were 50. Then convergent, divergent, expansive findings were triangulated from the quantitative and qualitative data analysis.Result: Most common type of animal was dog (74%) and most common category of the wound was category 2 (70%) followed by category 3 (30%). Most common site of exposure was leg (58%). Most common place of first visit after animal bite was health facility (94%). Around 46% of patients were referred from other places. Convergent findings revealed the most common type of animal that bit was dog. Divergent findings revealed the existence of cultural practices and consultations with local practitioner as the place of first visit after animal bite. Expansive findings revealed suggestions of preventing animal bites and decreasing referral of patients with animal bite.Conclusion: Most common type of bite was dog-bite. Most common site of exposure was lower extremity of the body. Category 2 bite was the most common. They gave important suggestions to prevent future animal bites and to decrease referral of the animal bite injury patients from the periphery to this hospital.